(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
This article discusses the issues of comprehensive quality assessment of double-layer and combined knitted fabrics intended for outerwear. An integral approach to quality assessment is proposed, taking into account structural, parametric, physical-mechanical, and performance indicators. Variants of imported knitted fabric samples are compared, and the advantages of rational structures are substantiated. The results demonstrate the possibility of implementing resource-saving technologies in knitwear production.